SINCAN Assessment and Best Innovation Assistance as a Form of Public Service Innovation in Bondowoso District, East Java - Muhammady, Iffan G.E.; Rizkika, Haressa Lintang; wicaksono, itok; kholifah, emy; maulana, akbar; Hamdi, HS; Kudus, Muhammad Zefri (Universitas Muhammadiyah Jember, 2025)
This community service program aims to strengthen the capacity of 23 sub-districts in Bondosowo Regency to meet the SINCAN (Sistem Informasi Kecamatan) standards set by the East Java Provincial Government. The main challenges include uneven technological infrastructure, low human resource capacity, and limited innovation documentation. Through a mixed-method approach involving training, integrated data hub development, and 360-degree assessments, the program successfully improved the average SINCAN score from 68 (2023) to 78 (2024). The innovation